2023
DOI: 10.4314/wiojms.v21i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial reef structures and coral transplantation as potential tools for enhancing locally-managed inshore reefs: a case study from Wasini Island, Kenya

Abstract: Many severely degraded reefs in the western Indian Ocean region show no signs of natural recovery and have remained for decades as barren, unconsolidated coral rubble fields with depleted commercially important fish groups. Consequently, several restoration techniques have been designed and developed to mitigate the localized impacts on coral reefs. Evaluating the efficacy of combined use of artificial reef structures and coral transplantation in enhancing habitat and recovery of key functions in severely degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition, this material showed a more stable response than other tested materials, such as Bioferment (according to the author's observation in the field). This could be related to the physical-chemical stability of the material [20,23,24,50], which is an important aspect for the restoration of marine ecosystems as hard materials increase coral transplant survival [51]. Materials must be durable during submersion and removable from the sea bottom, as required by some legislation in European countries (i.e., Spain or Italy).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this material showed a more stable response than other tested materials, such as Bioferment (according to the author's observation in the field). This could be related to the physical-chemical stability of the material [20,23,24,50], which is an important aspect for the restoration of marine ecosystems as hard materials increase coral transplant survival [51]. Materials must be durable during submersion and removable from the sea bottom, as required by some legislation in European countries (i.e., Spain or Italy).…”
Section: Discussionmentioning
confidence: 99%
“…The algae easily attached to the BPC's surface, leading to more frequent grazing activities by a group of herbivore fish (Graham and Nash 2013;Knoester et al 2019;Wilson et al 2021). A previous study showed reef fish also quickly populated the artificial reef structures, which was three times greater than those observed on natural reefs after two years in Kenya (Mwaura et al 2022). Carnivorous fish slowly increased, albeit not too significantly, from 25 Kg/Ha in February 2022 to 74 Kg/Ha in January 2023.…”
Section: Fish Biomassmentioning
confidence: 96%
“…This indicates coral rehabilitation effectively increases reef complexity (Hein et al 2020). The percentage of coral cover on artificial reef structures in Wasini Island, Kenya, rose significantly from 17% one year after fragments were first attached to 41% after two years (Mwaura et al 2022).…”
Section: Coral Survivorshipmentioning
confidence: 96%